Abiotic and Human Drivers of Reef Habitat Complexity Throughout the Main Hawaiian Islands - Asner, Gregory P.; Vaughn, Nicholas R.; Foo, Shawna A.; Shafron, Ethan; Heckler, Joseph; Martin, Roberta E. (Frontiers in Marine Science, 2021)
Reef rugosity, a metric of three-dimensional habitat complexity, is a central determinant of reef condition and multi-trophic occupancy including corals, fishes and invertebrates. As a result, spatially explicit information on reef rugosity is needed for conservation and management activities ranging from fisheries to coral protection and restoration. Across archipelagos comprising islands of varying geologic stage and age, rugosity naturally varies at multiple spatial scales based on island emergence, subsidence, and erosion. Reef rugosity may also be changing due to human impacts on corals such as marine heatwaves and nearshore coastal development. Using a new high-resolution, large-area mapping technique based on airborne imaging spectroscopy, we mapped the rugosity of reefs to 22 m depth throughout the eight Main Hawaiian Islands. We quantified inter- and intra-island variation in reef rugosity at fine (2 m) and coarse (6 m) spatial resolutions, and tested potential abiotic and human drivers of rugosity patterns. We found that water depth and reef slope remain the dominant drivers of fine- and coarse-scale rugosity, but nearshore development is a secondary driver of rugosity. Our results and maps can be used by fisheries management and reef conservations to track geologic versus human impacts on reefs, design effective marine managed areas, and execute activities to improve reef resilience.